Divided memory : the Nazi past in the two Germanys - Herf, Jeffrey, 1947- (Harvard University Press, 1997)
A significant new look at the legacy of the Nazi regime, this book exposes the workings of past beliefs and political interests in how - and how differently - the two Germanys have recalled the crimes of Nazism, from the anti-Nazi emigration of the 1930s through the establishment of a day of remembrance for the victims of National Socialism in 1996.